B1.3 The development and evaluation of a physiotherapy led respiratory outpatient clinic at great ormond street hospital (gosh). (4th October 2017) - Hill, L; Edel, L
Abstract : Background: Respiratory physiotherapy is an essential component in the management of many medical conditions and should be offered to these patients. Physiotherapy may involve airway clearance and cough enhancement, breathlessness management and symptom control, exercise testing and advice. 1 Twelve months ago consultant led respiratory clinics at GOSH had no dedicated physiotherapy input. The outpatients referred were seen if possible on the day but more often were referred to local services. Patients were receiving less specialist respiratory physiotherapy and the Trust was losing the potential to generate income. As a result, a physiotherapy led respiratory outpatient clinic was set up. Aim: To evaluate and discuss the outcome of developing a physiotherapy led respiratory outpatient clinic. Methods: The clinic, RESPPT, is on the 1 st and 3rd Monday of each month and is led by two specialist respiratory physiotherapists. A total of up to 8 patients can be seen, 2 new patients and 6 follow ups. Two rooms were secured for use in the physiotherapy department. Referrals were accepted from a consultant in any speciality at GOSH. Results: At 12 months, 138 patients had been referred to RESPPT, 53% neuromuscular, 35% general respiratory and 12% other. The clinic currently has a 12 week referral to treatment waiting time. Interim results from a parent/carer satisfaction survey show all patients were either satisfied or highly satisfied with the service. Conclusion: The physiotherapy led respiratory outpatient clinic has been perceived to be a successful new service. Potential development for the clinic includes; increasing frequency of clinics, requesting diagnostic tests and providing non-medical prescribing services. Further evaluation is planned to investigate if the clinic has reduced length of inpatient stays and has decreased hospital admissions for respiratory exacerbations. Reference: